I did a new thing : 30 days to living free - Brown, Tabitha (William Morrow, an imprint of HarperCollins Publishers, 2024)
Years ago, Tabitha Brown started a 30-day personal challenge that she called "I Did a New Thing!" The challenge was simple. Every day she would do something she'd never done before. In this book, Tab shares her own stories and those of others, alongside gentle guidance and encouragement to create these incredible changes for yourself and see what good can come from them.